Uji Efektivitas Perangkap Feromon Terhadap Hama Spodoptera exigua Hubner dan Intensitas Kerusakan Pada Tanaman Bawang Merah (Allium cepa var ascolonicum) - Betty Sahetapy; Saartje H. Noya (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2026)
Spodoptera exigua Hubner is one of the major pests of shallot plants causing significant yield losses. This study aimed to evaluate the effectiveness of Exi pheromone traps against S. exigua populations and damage intensity on shallot (Allium cepa var. ascalonicum L.) in Taeno Atas Hamlet, Teluk Ambon District, Central Maluku. The study employed a Completely Randomized Design consisting of two treatments, namely pheromone traps (PF) and yellow traps + pheromone (PKF), with four replications each. Observations were conducted for eight weeks on the number of trapped imagoes and plant damage intensity. Data were analyzed using analysis of variance followed by the Honestly Significant Difference (HSD) test at a 5% significance level. The results showed that pheromone traps were significantly more effective in capturing S. exigua imagoes than yellow traps + pheromone. The highest average imago catch was recorded in PF treatment with 15.7 individuals, while PKF captured 9 individuals. The lowest damage intensity was observed in PF treatment (11.31%), whereas the highest occurred in the control treatment (15.62%). Trap effectiveness was influenced by pheromone volatility, which attracted male imagoes through chemical communication during mating behavior. The use of Exi pheromone has the potential to become an environmentally friendly technology in Integrated Pest Management (IPM) systems to suppress S. exigua populations on shallot crops.